Recurrent Placental Transcriptional Profile With a Different Histological and Clinical Presentation: A Case Report. (December 2019) - Leavey, Katherine; Cox, Brian J; Cargill, Yvonne; Grynspan, David
Statistically, patients with severe pregnancy complications are at risk of recurrent complications, but it is less understood if patients present with similar or different placental pathologies in subsequent pregnancies. In this case report, we describe 2 consecutive adverse pregnancies in the same woman 4 years apart. The first pregnancy was diagnosed as early-onset preeclampsia and hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome, with placental maternal vascular malperfusion features, such as syncytial knots and accelerated villous maturity. In contrast, the second pregnancy was associated with normotensive fetal growth restriction and placental "immunological" lesions, such as massive perivillous fibrin deposition and chronic intervillositis. However, based on the expression of FLT1, LIMCH1, and TAP1 by quantitative polymerase chain reaction, the placentas from both pregnancies were found to exhibit an "immunological" transcriptional signature. This suggests that this small panel of gene expression markers may be able to predict the future reoccurrence of an immunological placental pathology despite no histological evidence within the first pregnancy. These results call for more studies looking at paired pregnancies of individuals with recurrent obstetric complications and confirm the importance of assessing matched transcriptional and histopathological placental information.